Gene expression profiling of primary fibrochondrocyte cultures in traumatic and degenerative meniscus lesions. (16th March 2021) - Aydın, Nuri; Karaismailoğlu, Bedri; Alaylıoğlu, Merve; Gezen-Ak, Duygu; Şengül, Büşra; Candaş, Esin; Yılmazer, Selma; Dursun, Erdinç
Purpose: This study aimed to investigate how fibroblastic and chondrocytic properties of human meniscal fibrochondrocytes are affected in culture conditions according to the type of meniscal pathology and localization, and to provide basic information for tissue-engineering studies. Methods: Primary fibrochondrocyte cultures were prepared from meniscus samples of patients who had either traumatic tear or degeneration due to osteoarthritis. Cultures were compared in terms of mRNA expression levels of COL1A1, COL2A1, COMP1, HIF1A, HIF2A, and SOX9 and secreted total collagen and sulfated sGAG levels according to the type of meniscal pathology, anatomical localization, and the number of subcultures. Results: mRNA expression levels of COL1A1, COMP1, HIF1A, HIF2A, and SOX9 were found to be increased in subsequent subcultures in all specimens. COL1A1 mRNA expression levels of both lateral and medial menisci of patients with traumatic tear were significantly higher than in patients with degenerative pathology, indicating a more fibroblastic character. P1 subculture of lateral and P3 or further subculture of medial meniscus showed more fibroblastic characteristics in patients with degenerative pathology. Furthermore, in patients with degenerative pathology, the subcultures of the lateral meniscus (especially on the inner part) presented more chondrocytic characteristics than did those of medial meniscus. Conclusions: The mRNA expression levels of the cultures showed significant differences according to the anatomical localization and pathology of the meniscus, indicating distinct chondrocytic and fibroblastic features. This fundamental knowledge would help researchers to choose more efficient cell sources for cell-seeding of a meniscus scaffold, and to generate a construct resembling the original meniscus tissue.